Risk factors for rebleeding in patients with peptic ulcer bleeding - M V Valeev (Kazanskij Medicinskij Žurnal, 2020)
Aim. To analyze the results of treatment of patients with ulcerative bleeding, to identify the main risk factors for rebleeding in patients with peptic ulcer bleeding.